Pengaruh Work Engagement, Job Satisfaction dan Employee Empowerment terhadap Organizational Commitment pada Karyawan Perusahaan Jasa Transportasi di Kalimantan Barat - Arif Muttaqin; Wiwik Robiatul Adawiyah (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
This study examines the effects of work engagement, job satisfaction, and employee empowerment on organizational commitment among employees of a transportation service company. The research was motivated by the need to understand psychological and organizational factors that strengthen employee loyalty in a dynamic service industry. A quantitative approach was applied using a survey of 130 respondents selected through total sampling. Data were analyzed using multiple linear regression with SPSS to test the proposed hypotheses. The findings indicate that work engagement, job satisfaction, and employee empowerment each have a positive and significant effect on organizational commitment. Among these variables, job satisfaction shows the strongest influence, suggesting that fair treatment, supportive supervision, and opportunities for development are key drivers of employee commitment. The results imply that management should prioritize strategies to enhance employee satisfaction, foster meaningful work involvement, and expand empowerment practices to strengthen long-term organizational attachment. These findings contribute empirical evidence on commitment development in transportation service companies and provide practical guidance for human resource policies.